Analysis of Digital Payment and Financial Literacy as Instruments for Improving Financial Accountability and Business Performance in Modern Coffee Shops in Central Java - Ermaini Ermaini; Muhamad Ammar Muhtadi; Rani Eka Arini (Westscience Press, 2026)
This study examines the effects of digital payment adoption and financial literacy on financial accountability and business performance among modern coffee shops in Central Java. A quantitative explanatory design was employed using primary data collected from 125 coffee shop owners and managers through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using IBM SPSS Statistics version 25 through descriptive statistics, validity and reliability testing, classical assumption testing, multiple linear regression, t-tests, F-tests, and coefficient of determination analysis. The results indicate that digital payment adoption has a positive and significant effect on financial accountability, with a standardized coefficient of 0.396 and a significance value below 0.001. Financial literacy also positively affects financial accountability, with a standardized coefficient of 0.451 and a significance value below 0.001. Together, digital payment adoption and financial literacy explain 61.0% of the variance in financial accountability. Digital payment adoption, financial literacy, and financial accountability also have positive and significant effects on business performance, with standardized coefficients of 0.247, 0.301, and 0.416, respectively. The second regression model explains 71.4% of the variance in business performance. Financial accountability demonstrates the strongest influence on business performance, indicating that accurate records, transparent reporting, and effective financial control are essential for improving organizational outcomes. The study concludes that integrating digital payment systems with strong financial literacy can enhance financial accountability and support sustainable business performance among modern coffee shops.